Genetics and Microchimerism in the Contemporary Society: An Exegetical Discourse - Saheed Adewale Badmus; Jalaludeen Shuaib Assayouti; Halimah Olajumoke Omotosho; Abdulmumeen Abdulmaleek Elejo (Penerbit Hellow Pustaka, 2026)
The evolving nature of scientific issues in the contemporary society makes the world a complex terrain not only socially but also religiously. Among these issues are genetics and microchimerism which are related to individuals and the society. However, both concepts have become part and parcel of human life in the contemporary society as a result of technological advancement and civilization. It is important to note that the Muslims are being affected one way or the other through marital affairs. Thus, this paper delves into the concept of genetics and microchimerism by exploring its implications in the contemporary Muslims. The study adopts analytical method of research. Through this, it aims to analyze the concept of genetic and microchimerism, explore its implications on individuals and the society. It also provides insights into the ethical and moral dimensions of this phenomenon from the Quranic perspectives through the explanations of Mufassirūn in their exegetical works. The findings of this research highlight the need for a nuanced understanding of genetic and microchimerism, emphasizing the importance of addressing the ethical, social, and identity-related concerns associated with this phenomenon. This paper suggests further research on the intersection of genetics; Microchimerism and Islamic Jurisprudence. It also recommends the creation of awareness programme to enlighten the public on the ethical and societal implications of genetics and Microchimerism as well highlighting the limitation of DNA testing in determining child paternity.